Need for nutritional support, eating-related distress and experience of terminally ill patients with cancer: a survey in an inpatient hospice. Issue 3 (6th January 2015) - Amano, Koji; Maeda, Isseki; Morita, Tatsuya; Tatara, Ryohei; Katayama, Hirofumi; Uno, Teruaki; Takagi, Ibuki
Abstract : Objectives: Cancer cachexia creates a large burden for terminally ill patients with cancer. The main causes are a lack of knowledge of cancer cachexia and unsuccessful attempts to increase body weight. The role of nutritional support has not been clarified, and patients' eating-related distress is poorly understood. There has been no study investigating into needs for nutritional support in an inpatient hospice. The primary aim of this study was to explore needs for nutritional support, eating-related distress and patients' experiences. Methods: A survey was conducted involving 60 patients with advanced cancer in an inpatient hospice. We first asked about need for nutrition therapy in the inpatient hospice. We then asked whether patients had unmet needs for four items. The last question was composed of 19 items concerning patients' experience of eating-related distress. Results: Thirty-seven patients responded (62%). Most of the patients, 28 of 37 (76%), had general unmet needs for nutrition therapy for cancer cachexia, and more than half needed specific support, such as 'attention' and 'explanation'. The top 5 of the 19 items were mainly about daily diet, nutrition and losing weight. Of these, the top four belonged to the group of coping strategies and the fifth to the group of mechanisms originating from patients themselves. Conclusions: A number of terminally ill patients with cancer admitted to an inpatient hospice had need for nutritional support and experienced high levels of eating-related distress.